Optimasi Pendistribusisan Air Menggunakan Improved Zero Point Method (Studi Kasus di PDAM Tirta Kepri) - Kurnia Apridita Utami; Media Rosha; Meira Parma Dewi (Journal of Mathematics UNP, 2019)
Abstract – Clean water is a basic necessity for human beings that must be fulfilled. One of business entities enganged in the activities of the fulfillment of the need of clean water is PDAM Tirta Kepri. In its activities, some constraints are found that can increase distribution cost. To minimize the distribution cost at PDAM Tirta Kepri, Improved Zero Point Method is used. This method is a method to optimize transportation problem that can provide optimum solution directly without the aid of modification of other methods. The result of the calculation of the cost of the distribution done by PDAM Tirta Kepri from two springs and four distribution areas is Rp 20.397.467,12. By using the Improved Zero Point Method, the cost obtained is Rp 20.198.416,44,- Therefore, Improved Zero Point Method can optimize the distribution cost problem at PDAM Tirta Kepri  without the aid of modification from other methods on transportation problem table.Keywords – Optimization, IZPM, Distribution of Water.